HYDROGEN PEROXIDASE ENZYME ACTIVITY AT DIFFERENT CONCENTRATIONS OF BSA - İLHAN, Ahmet and KÖKBAŞ, Umut and KAYRIN, Levent (Göbeklitepe Medical Science Journal, 2022)
Cross-linked enzymes are more stable at a certain temperature than free enzymes. Bovine serum albumin (BSA), which has a large number of amine groups, provides a strong binding between enzyme aggregates, thus leading to increased activity and stability of the bioactive layer. The enzyme-BSA mixture becomes more stable after covalent bonding with a crosslinking agent such as glutaraldehyde. It was prepared by immobilizing HRP enzyme, BSA, gelatin and glutaraldehyde on the gold electrode with the help of UV light. Four different electrodes were prepared using different amounts of BSA at 7.5 mg, 15 mg, 30 mg and 60 mg concentrations for each electrode. Electrochemical measurements were carried out with four different electrodes prepared. Glutaraldehyde binds to the BSA polymer, which has a higher affinity than the enzyme, reducing the tight covalent cross-links caused by BSA on the HRP and ensuring the continuation of the enzyme activity. It has been observed that the BSA concentration to be used is important in the performance of enzymes in electrochemistry. It should not be overlooked that different BSA concentrations are an important factor in electrochemical studies.